APPLICABILITY OF LEWIN'S CHANGE MANAGEMENT MODEL FOR OPTIMIZATION MANAGEMENT FUNCTION IN NURSING DELEGATION BETWEEN HEAD NURSE AND TEAM LEADER: A MINI PROJECT IN JAKARTA MILITARY HOSPITAL: DOI: https://doi.org/10.35654/ijnhs.v2i2.136 - Aris Teguh; Rr. Tutik Sri Hariyati; Titiek Muhaeriwati (International Journal of Nursing and Health Services (IJNHS), 2019)
The role of nurses in health care systems is diverse, included being a health care provider to clients, client advocates, educators for clients and families, and nursing service managers. One strategy that can be applied in managerial nursing is delegation. The goal of this study was to assess the applicability of Kurt Lewin's change management method to analyse the management function in nursing delegation between head nurse and team leader. This study was conducted in one of the Jakarta Military Hospital by conducting a mini project consisting of case reports using a fishbone diagram approach, solving problems using Plan-Do-Check-Action (PDCA) tools starting with Plan Of Action (POA), implementation, evaluation, and follow-up. The results of the identification showed that the head of the room in carrying out the delegation was not optimal, included documentation in the delegation book that was not optimal, delays in filling, non uniformity in the format of delegation books in the room, and not understanding due to lack of standardization and control from superiors. Guidelines are used as a reference in delegating nursing to the head of the hospital room, and the documentation of nursing delegates is done correctly because delegates work better when the reporting structure is clear. In conclusion, application fishbone diagram, lewin's change management model, and PDCA cycle can optimize management function in nursing delegation between head nurse and team leader in Jakarta Military Hospital. Recommendations are given to the nursing department, head of the room, team leader, and executive nurses to increase self-awareness, knowledge, and ability in delegating nursing.